Perceptions of justice and hierarchies of rape: rethinking approaches to sexual violence in Eastern Congo from the ground up - Aroussi, Sahla (International journal of transitional justice, 2018)
Based on extensive fieldwork in South Kivu in eastern Democratic Republic of the Congo (DRC), this article considers the question of justice for survivors of sexual violence from the ground up. It argues that survivors of rape by armed groups or civilians in the DRC primarily conceive of justice as economic assistance and have limited interest in the prosecution of perpetrators. Such emphasis on economic assistance cannot be separated from the reality of poverty in which survivors live and local perceptions and practices of justice that are rooted in the concept of reparation. At the same time, survivors’ reluctance to pursue formal justice must be understood in the light of the inaccessibility of the Congolese criminal justice system and its failure to play a positive role in society. The article concludes by offering some recommendations for actors and scholars in this area.